Regulation of I𝜅B𝛼 Function and NF-𝜅B Signaling: AEBP1 Is a Novel Proinflammatory Mediator in Macrophages - Amin Majdalawieh; Hyo-Sung Ro (Hindawi Limited, 2010)
NF-𝜅B comprises a family of transcription factors that are critically involved in various inflammatory processes. In this paper, the role of NF-𝜅B in inflammation and atherosclerosis and the regulation of the NF-𝜅B signaling pathway are summarized. The structure, function, and regulation of the NF-𝜅B inhibitors, I𝜅B𝛼 and I𝜅B𝛽, are reviewed. The regulation of NF-𝜅B activity by glucocorticoid receptor (GR) signaling and I𝜅B𝛼 sumoylation is also discussed. This paper focuses on the recently reported regulatory function that adipocyte enhancer-binding protein 1 (AEBP1) exerts on NF-𝜅B transcriptional activity in macrophages, in which AEBP1 manifests itself as a potent modulator of NF-𝜅B via physical interaction with I𝜅B𝛼 and a critical mediator of inflammation. Finally, we summarize the regulatory roles that recently identified I𝜅B𝛼-interacting proteins play in NF-𝜅B signaling. Based on its proinflammatory roles in macrophages, AEBP1 is anticipated to serve as a therapeutic target towards the treatment of various inflammatory conditions and disorders.